2013
DOI: 10.1111/ajps.12067
|View full text |Cite
|
Sign up to set email alerts
|

Civil War and Social Cohesion: Lab‐in‐the‐Field Evidence from Nepal

Abstract: We study effects of wartime violence on social cohesion in the context of Nepal's 10-year civil war. We begin with the observation that violence increased levels of collective action like voting and community organization-a finding consistent with other recent studies of postconflict societies. We use lab-in-the-field techniques to tease apart such effects. Our causalidentification strategy exploits communities' exogenous isolation from the unpredictable path of insurgency combined with matching. We find that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
251
3
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 385 publications
(276 citation statements)
references
References 43 publications
20
251
3
2
Order By: Relevance
“…In a study of Nepalese society, Gilligan, Pasquale, and Samii (2014) found that members of communities with greater exposure to violence during the 1996-2006 civil war, between governmental forces and Maoist revolutionaries, exhibited greater levels of cooperation when interacting with each other: three years post-conflict, they were more trustworthy in a Trust game, more willing to contribute to the common pot in the Public Goods game, and they reported being more active in community organizations.…”
Section: Other Country Cases: Uganda Burundi Georgia Nepal and Otmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of Nepalese society, Gilligan, Pasquale, and Samii (2014) found that members of communities with greater exposure to violence during the 1996-2006 civil war, between governmental forces and Maoist revolutionaries, exhibited greater levels of cooperation when interacting with each other: three years post-conflict, they were more trustworthy in a Trust game, more willing to contribute to the common pot in the Public Goods game, and they reported being more active in community organizations.…”
Section: Other Country Cases: Uganda Burundi Georgia Nepal and Otmentioning
confidence: 99%
“…The data were gathered among a sample of children six months after the brief August 2008 war with Russia over South Ossetia. As in Sierra Leone, the authors found evidence of a differential treatment of in-group and out-group: participants who were more affected by the conflict were less selfish and more inequality averse towards ingroup members (their classmates) as compared to their less affected peers, but no such effects on behavior towards out-group was found.In a study of Nepalese society, Gilligan, Pasquale, and Samii (2014) found that members of communities with greater exposure to violence during the 1996-2006 civil war, between governmental forces and Maoist revolutionaries, exhibited greater levels of cooperation when interacting with each other: three years post-conflict, they were more trustworthy in a Trust game, more willing to contribute to the common pot in the Public Goods game, and they reported being more active in community organizations. …”
mentioning
confidence: 99%
“…This is surprising as research (unrelated to sexual violence) suggests that collective coping processes can be effective strategies for overcoming trauma (Bowles 2008;Lyons et al 1998). Recent microlevel studies find evidence that exposure to (nonsexual) political violence tends to make people more altruistic (Gilligan, Pasquale, and Samii 2013;Voors et al 2012) and politically engaged (Blattman 2009;Annan et al 2011). Are there similar accounts for individuals, families, and communities who have been exposed to CRSV?…”
Section: Intracommunal Cleavagesmentioning
confidence: 99%
“…Ruggeri, Dorussen, andGizelis (2016a, 2016b) show that robust peacekeeping limits the conflict episodes in specific localities, while Gleditsch and Beardsley (2015) demonstrate how peacekeeping avoids conflict from engulfing countries. Fieldwork and field experiments use increasingly sophisticated research designs to address concerns of peacekeeping and the 'peacekept' directly (Fortna 2008b;Gilligan, Pasquale, andSamii 2014, Gilligan et al 2012;Mvukiyehe and Samii 2012). Ethnographic research (Autesserre 2010(Autesserre , 2014 details peacekeeping practices and their failure to secure peace from the bottom-up.…”
Section: Introductionmentioning
confidence: 99%